Effect of fluoride varnish, sealants and caries infiltration in reducing the progression of proximal incipient caries in primary teeth. - Altounsi, Suha. (2017)
Abstract: Objective: The reduction or arrest of proximal white spot lesions in primary teeth due to fluoride varnish, sealants, and resin infiltrants has been reported in previous studies. However, none of these studies reported which treatment gives the best results. Therefore, the aim of this study was to find the most effective treatment approach by comparing white spot lesion progression after treatment with fluoride varnish, sealants, and infiltrants. Materials and Methods: Artificial proximal white spot lesions were created on 60 extracted primary teeth. Specimens were sectioned perpendicularly across the lesion in two halves. Fluoride varnish (Vanish 5% Sodium Fluoride White), sealant (Helioseal Clear), and resin infiltration (ICON) were applied to both halves. One of the halves was subjected to a demineralizing solution for five days. The other half was used as a baseline. Lesion progression was measured by comparing the mineral loss of the paired halves at eight depth points located within lesion area. This was done using the Cross-Sectional Knoop Microhardness Test. Results: Differences in caries progression between the four groups (A: no treatment, B: fluoride varnish, C: sealants, and D: resin infiltrants) were statistically significant at three depth points 125µm (P= .005), 175µm (P = .001), and 200µm (P = .003). At a depth of 175µm, caries progressed more significantly in the fluoride varnish group (7.8%) compared to the sealant (-0.5 %) (P < .001) and the infiltrant groups (-1.7%) (P < .001). No significant difference was found between the sealant and infiltrant groups (P = .94), or between the fluoride varnish and the control groups (P = .118). Conclusion: Based on this study's results, the following conclusions can be made: 1- Observing proximal incipient caries or applying fluoride varnish did not reduce caries progression. 2- Sealants (Helioseal) and resin infiltrants (ICON) were capable of significantly reducing the progression of white spot lesions in proximal surfaces when compared with the application of fluoride varnish. The use of sealants and infiltrants seem to be promising novel methods for reducing and inhibiting proximal caries progression in primary teeth.; Thesis (M.S.)--Tufts University, 2012.; Submitted to the School of Dental Medicine.; Advisors: Perry Ronald, and Masly Harsono.; Committee: Alfred Rich, Matthew Finkelman, and Cheen Loo.; Keyword: Dentistry.